2006
DOI: 10.1097/01.bcr.0000226260.17523.22
|View full text |Cite
|
Sign up to set email alerts
|

National Burn Repository 2005: A Ten-Year Review

Abstract: In the early 1990s, the American Burn Association (ABA) started its first burn registry development initiatives. The impetus for the registry development software originated from several directions, including the following: (1) the recognition that national registries were widespread and of proven benefit; (2) growing demands from accrediting institutions, payers, and patient advocacy groups for objective and verifiable data regarding patient costs, treatments, and outcomes; and (3) the shift toward "evidence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(73 citation statements)
references
References 3 publications
4
67
2
Order By: Relevance
“…Amputations were performed in 6.0% of cases. These characteristics are similar to data reported in the National Burn Registry (NBR) for the period 1995 -2005 with records on more than 126,000 individuals admitted to hospitals in 30 states and the District of Columbia with burn injury (35).…”
Section: Study Populationsupporting
confidence: 70%
“…Amputations were performed in 6.0% of cases. These characteristics are similar to data reported in the National Burn Registry (NBR) for the period 1995 -2005 with records on more than 126,000 individuals admitted to hospitals in 30 states and the District of Columbia with burn injury (35).…”
Section: Study Populationsupporting
confidence: 70%
“…Over 440,000 children receive medical attention for burn injuries each year in the United States (3). With approximately 1,100 children dying of burnrelated injuries in the United States every year (4), severe burns represent the third most common cause of death in the pediatric patient population (5), and account for a significant number of hospital admissions in the United States (6,7). A severe burn, therefore, represents a devastating injury affecting nearly every body organ system and leads to significant patient morbidity and mortality (8).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to patients burned prior to 1970, people now more commonly survive burn injuries. Before 1970, a burn injury greater than one third of the total body surface area (TBSA) was usually fatal [3], whereas a recent 10 year review of the National Burn Repository database showed that a 60-70% TBSA burn now has a survival rate of approximately 53% [4]. While advances have clearly been made in increasing the survival rates of burn patients, this success has not necessarily led to an improved ability to alleviate the longer-term symptoms of burn injury.…”
Section: Introductionmentioning
confidence: 99%